Transformation of Ponpes At-Tanwir Bojonegoro from Salaf to Modern - Anam , Choirul (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
KH. Muhammaad Sholeh is a founder, caregiver and leader of the At-Tanwir Talun Islamic boarding school, Sumberejo District, Bojonegoro Regency, he is able to bring very good changes to the residents around Talun village. In this study, the researcher used a qualitative type of research with a descriptive historical approach. In this study, researchers used sources in the form of heritage books, written works, and other supporting documents. The purpose of this study was to determine the transformation of the development of the Islamic boarding school at-tanwir from traditional to modern boarding schools during the KH. Muhammad Salih. The results of this research are: Pondok Pesantren Attanwir is present in a society that is contrary to Islamic teachings. With the struggle of KH. Muhammaad Sholeh, he was able to little by little to make changes to the behavior of the people of Talun village. The presence of Pondok Pesantren At-Tanwir is a testament to the persistence of KH. Muhammad Sholeh to present a boarding school. In its growth, Pondok Pesantren At-Tanwir has a desire to adapt to the development of the modern world out there. In 1951, there was a classical learning method, namely by opening a Madrasah Ibtidaiyah and in the following year it grew into various Islamic educational institutions but did not eliminate the identity of traditional education.